DEVELOPING STUDENTS SPEAKING SKILL TROUGH GUESSING GAMES - Kade Sukerni Ida Ayu; Oka Purnami Ida Ayu (Yavana Bhasha : Journal of English Language Education, 2019)
This study aims at describing how the students can improve their speakingskill and that also part of the teachers’ job. A teacher is expected to have rightteaching techniques to provide students with appropriate teaching materials and tocreate a positive classroom environment. The data of this study were collectedthrough observations, planning, action, and reflection, some of the researchers wereconducted in two cycles. The data were obtained by interviewing the Englishteachers and students. The result of this study showed that the speaking skill canimproved through guessing games. These were confirmed by the data on thefinding and discussion in the researchers’ article